Proteína bruta, energia digestível e densidade de estocagem do ciclídeo ornamental acará-bandeira (Pterophyllum scalare) - OLIVEIRA, Wallace Henrique de (2009)
In order to increase the knowledge on the production of angelfish ornamental cichlids (Pterophyllum scalare), two experiments were conducted at the School of Veterinary Medicine and Zootecnia of the UFT, Araguaína /TO, between october 2008 and january 2009, using 400 angelfish juveniles. Each experiment had a duration of 42 days, with fish divided into 16 aquariums, fed ad libitum, room temperature, 20% daily water renewal. The work was organized in a factorial scheme 2x2, with: two levels of crude protein (CP, 29 and 32%) and two angelfish strains (gold and marmorate), with 160 juveniles from 350+4.0 mg in design randomized blocks, in the first experiment; two levels of digestible energy (DE, 2.9 and 3.4 Mcal / kg) and two stocking rate (10 or 20 fish/aquarium), with 240 fishes of 260+4.2 mg in a completely randomized design in the second. Means were compared by Tukey test at 5%. Weight gain (WG), apparent feed intake (AFI), food conversion rate (FCR), protein efficiency rate (PER), specific growth rate in weight (WSGR) and length (LSGR), Fulton condition factor and carcass composition were avaliated. It was found that the levels of CP did not differ in the parameters studied (P>0.05) and the marmorate strain was more efficient than gold strain by presenting best means of WG, AFI, FCR, PER, WSGR, LSGR (P<0.05). Also, fish fed 3.4 Mcal of DE/kg showed better means WG, AFI, FCR, PER, WSGR and LSGR (p<0.05). There was no significant difference in parameters of growth, consumption and conversion between the stocking rate (p>0.05). It was concluded that angelfish juveniles have similar performance when fed with 29 or 32% CP and better in the diets with 3.4 Mcal of DE/kg than with 2.9 Mcal/kg. Also, marmorate strain was better than gold strain and at this stage of development, can be created in stocking rate of one fish for every three liters of water, with 20% of daily water renewal